2020
DOI: 10.1111/myc.13053
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of nosocomial candidaemia in neonates, infants and children: A multicentre study in Iran

Abstract: Summary Nosocomial bloodstream candidaemia is a life‐threatening fungal infection with high morbidity and mortality, especially among paediatric patients undergoing intensive immunosuppressive therapy. Limited data on the epidemiology of candidaemia and susceptibility profiles are available for Iran. To characterise candidaemia epidemiology, comorbidity risk factors, species distribution, and antifungal susceptibility profiles among paediatric patients in Iran. This observational cross‐sectional study enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…In this study we compared the performance of Vitek 2 and 21-plex PCR for yeast species identification in an epidemiological study of yeast BSIs in Iran. In our epidemiological study, C. albicans was the most prevalent Candida species isolated; this result is consistent with the findings of a previous studies conducted in paediatric patients in Tehran [ 7 , 26 ]. However, we found that C. glabrata was the second most prevalent Candida species, followed by C. parapsilosis, while Mirhendi et al found that C. parapsilosis was the second most prevalent cause of candidaemia [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study we compared the performance of Vitek 2 and 21-plex PCR for yeast species identification in an epidemiological study of yeast BSIs in Iran. In our epidemiological study, C. albicans was the most prevalent Candida species isolated; this result is consistent with the findings of a previous studies conducted in paediatric patients in Tehran [ 7 , 26 ]. However, we found that C. glabrata was the second most prevalent Candida species, followed by C. parapsilosis, while Mirhendi et al found that C. parapsilosis was the second most prevalent cause of candidaemia [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Candidemia patients (usually with underlying conditions, such as diabetes, cancer, pulmonary and heart complications) mostly are admitted to ICUs. The overall crude mortality of 47.2% in our study is similar to that reported by other investigators from Iran [43][44][45] but considerably higher than the 26% quoted by Chen et al [46]. Sixty patients took at least one antifungal drug and the mortality rate for these patients was 38.3% (23/60; 38.3%).…”
Section: Discussionsupporting
confidence: 87%
“…However, infections caused by non-albicans Candida , such as C. parapsilosis , C. glabrata , C. tropicalis , C. krusei , and C. guilliermondii , have been increasing, usually reported in critically ill patients, sometimes with overlapping C. albicans infections. In addition, other emerging non-albicans species are described as challenging to properly identify, causing hard to treat infections ( Pfaller and Diekema, 2007 ; Wisplinghoff et al, 2014 ; Lamoth et al, 2018 ; Rodrigues et al, 2019 ; Ahangarkani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%